2004
DOI: 10.1093/jn/134.8.1958
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Deficiency Impairs Fetal Islet Development and Causes Subsequent Glucose Intolerance in Adult Rats

Abstract: To determine the role of vitamin A in fetal islet development, beta- and alpha-cell mass, apoptosis, and alpha- and beta-cell replication were measured in rats using a model of marginal vitamin A deficiency. Female rats before and during pregnancy and their offspring postweaning were fed a diet containing retinol as retinyl palmitate at a low marginal (LM, 0.25 mg/kg diet) or a sufficient (SUFF, 4.0 mg/kg diet) level. Fetal islet size, replication, apoptosis, and offspring glucose tolerance were examined. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 31 publications
0
54
0
4
Order By: Relevance
“…The output reads were aligned to the human reference genome (hg19) with STAR [18,19] and feature counting was done using feature Counts [20]. Raw data was normalised using trimmed mean of M-values and presented as Fragments Per Kilobase of Exon Per Million Fragments Mapped (FPKM) or transformed using into log2 counts per million using the voom-function secretion during acute exposure (<1 h) suggests that it also signals via a non-genomic mechanism that is independent of transcriptional regulation induced by nuclear retinoid acid receptors [11][12][13].…”
Section: Expression Of Gprc5c In Human Pancreatic Islets Analysed By mentioning
confidence: 99%
“…The output reads were aligned to the human reference genome (hg19) with STAR [18,19] and feature counting was done using feature Counts [20]. Raw data was normalised using trimmed mean of M-values and presented as Fragments Per Kilobase of Exon Per Million Fragments Mapped (FPKM) or transformed using into log2 counts per million using the voom-function secretion during acute exposure (<1 h) suggests that it also signals via a non-genomic mechanism that is independent of transcriptional regulation induced by nuclear retinoid acid receptors [11][12][13].…”
Section: Expression Of Gprc5c In Human Pancreatic Islets Analysed By mentioning
confidence: 99%
“…Also uncertain is the contribution of impaired glucose tolerance to diminished pancreatic β-cell function and mass associated with type 2 diabetes (5). GSIS relies on the pancreas, and pancreas development, islet formation, and function require normal vitamin A nutriture (6)(7)(8). Vitamin A restriction during development impairs islet development and promotes glucose intolerance in adult rodents.…”
mentioning
confidence: 99%
“…On the other hand, restricting vitamin A in mature diabetes-prone rats reduces diabetes and insulitis, possibly through enhancing glucose sensing and metabolism. Alltrans-retinoic acid (atRA), an activated metabolite of vitamin A, regulates pancreas development, and atRA does not enhance the incidence of diabetes in diabetes-prone rats fed a vitamin Adeficient diet (7,9,10). Although the contribution of vitamin A to pancreas development through atRA seems clear, mechanisms whereby vitamin A affects mature pancreas function have not been determined in depth, nor have the specific vitamin A metabolites been identified that contribute to GSIS control.…”
mentioning
confidence: 99%
“…These are summarized in Micronutrient status may also be suboptimal in the acute phase of recovery from injury, but improve over time. 55 Almost all of the above listed micronutrients have been linked to glycemic and/or lipid profiles, [58][59][60][61][62][63][64][65][66][67][68][69][70][71] but a detailed exploration of these deficiencies and their association with CMS risks of dysglycemia and dyslipidemia exceeds the scope of this monograph. In addition, only a few of these deficiencies have consistently been reported to be prevalent in persons with SCI over the last 10 years.…”
Section: Micronutrients and Alcoholmentioning
confidence: 99%